Redifinisi Agama - Fibry Jati Nugroho (Sekolah Tinggi Teologi SAPPI Ciranjang, 2017)
Definition of prevailing religion in general (world religions) have been constructed in such a manner in accordance with the concept of rulers. Before the import of religion comes, the local belief has gained a place and has fostered human society into a